STAT3 down‐regulation induces mitochondria‐dependent G2/M cell cycle arrest and apoptosis in oesophageal carcinoma cells. (March 2017) - Shao, Dan; Ma, Jie; Zhou, Chao; Zhao, Jia‐Nan; Li, Lu‐Lu; Zhao, Tong‐Jian; Ai, Xi‐Lei; Jiao, Ping
Summary: STAT3 is persistently activated in a wide variety of human tumours, and aberrant STAT3 activity promotes tumour growth, invasion and metastasis. To explore STAT3 down‐regulation in human oesophageal cancer cells, cell proliferation, apoptosis and mitochondrial mechanisms were explored in oesophageal carcinoma TE1 cell cultures. We demonstrate for the first time that STAT3 down‐regulation by RNAi is sufficient to inhibit oesophageal cancer cell proliferation inducing cell apoptosis. Further, we demonstrate that mitochondrial transmembrane potential is impaired thereby leading to collapsed mitochondrial membrane potential, abnormal mitochondrial membrane depolarization, nuclear DNA fragmentation and cell cycle G2/M arrest under the conditions of STAT3 down‐regulation. Thus, our results suggest that STAT3 inhibition is a valid approach to induce oesophageal carcinoma cell mitochondrial‐dependent apoptosis in therapeutic strategies against oesophageal cancers.